Application of the volume of fluid method with heat transfer to a two-shaft aero-engine bearing chamber - Bristot, Andrea (2018)
The innovations proposed for future civil aero engine concepts are likely to pose new challenges for the oil system. Higher cooling requirements and smaller core sizes mean that an effective use of oil is fundamental to secure the efficiency gains achievable with new designs. The introduction of accurate tools to predict the behaviour of air and oil flows is key to support this process.